Health Navigator intervention to address the unmet social needs of populations living with cancer attending outpatient treatment at a major metropolitan hospital in Australia: protocol for a mixed-methods feasibility trial - Sean Martin; Kate Neadley; Annabel Smith; Mark Boyd; Christopher Hocking; Cheryl Shoubridge (BMJ Open)
Introduction Integrating health and social care to address unmet social needs is an emerging priority for health systems worldwide. Screening and referral interventions for unmet social needs, also known as Health Navigator (HN) interventions, in healthcare settings have shown mixed but promising results, mostly due to a large variability in intervention design and outcomes assessed. Most HN interventions are implemented in primary care, despite evidence that disadvantaged populations face substantial barriers to accessing such care, and these interventions are limited in Australia. To address this gap, we designed a HN intervention to address the unmet social needs of a disadvantaged population living with cancer presenting at an outpatient cancer treatment facility in South Australia. To our knowledge, this paper presents a protocol for one of the first feasibility and acceptability studies of an HN intervention in an Australian healthcare setting.Methods and analysis We will conduct a single-centre study to explore the feasibility and acceptability of screening and referral for unmet social needs for patients attending an outpatient cancer clinic at a major metropolitan hospital serving a disadvantaged population in South Australia. Eligible participants are 18 years of age or older receiving treatment at the Northern Adelaide Cancer Centre, with an expected prognosis of minimum 6 months. During recruitment, a researcher will ask eligible participants to complete unmet social needs screening and baseline assessments. Participants with unmet social needs who request assistance will be connected with an HN. The HN will work with participants to prioritise their needs and provide referrals to community and government services with follow-up of over 6 months from enrolment. Post-HN intervention, all participants will be asked to complete repeat unmet social needs screening and repeat assessments. The primary criteria for determining feasibility success are: (1) recruitment rates, where 80% of eligible participants agree to unmet needs screening; (2) intervention uptake, where 80% of participants who report unmet social needs consent to assistance from a HN; (3) intervention completion, where 80% of participants receive HN assistance complete follow-up; (4) reasons for not completing intervention; and (5) participant and clinician acceptability of the intervention. Secondary outcomes include changes to unmet social needs and coping with cancer ability, quality of life and patient-reported experience measures. Thematic analysis will be applied to focus groups with clinicians and participants to assess intervention acceptability. Secondary clinical outcomes will be reported as effect size estimates for future trials. Based on previous work in this area, we will aim to recruit 350 participants. Study findings will be used to optimise recruitment and intervention components and develop suitable outcome measures for larger, randomised studies.Ethics and dissemination The protocol has ethical approval from the Central Adelaide Local Health Network Human Research Ethics Committee (approval ID: 16448). Findings will be disseminated in research publications and non-academic formats for a variety of audiences.Trial registration number Australian New Zealand Clinical Trial Registry (ACTRN12622000802707p).Protocol date and version: 07 June 2022, V1.